Geología de los cuadrángulos de Punchana, Remanso, San Martín de Soledad, Quebrada Esperanza, Río Yahuillo, Quebrada Lupuna, Río Yahuas, Primavera, Pebas, Río Atacuari, Río Cotuhé, Quebrada Chontadero, San Francisco , Chambira, Caballococha, San Juan de Cacao, Carolina, San Pablo de Loreto, San Pedro, Islandia, Isla Chinería y Lagogrande 5-s, 5-t, 5-u, 5-v, 6-s, 6-t, 6-u, 6-v, 7-s, 7-t, 7-u, 7-v, 8-s, 8-t, 8-u, 8-v, 9-s, 9-t, 9-u, 9-v, 9-x, 10-s – [Boletín A 133] - Zavala Carrión, Bilberto Luis (1999)
257 p., 22 mapas